2020
DOI: 10.1159/000506798
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Texture of Medial Pulvinar in Dementia with Lewy Bodies

Abstract: Introduction: Executive dysfunction is common in dementia with Lewy bodies (DLB). The pulvinar nucleus plays a role in executive control and synchronizes with cortical regions in the salience network that are vulnerable to Lewy pathology. Objective: We investigated the pulvinar subregions in patients with mild DLB and their associations with executive function. Methods: The sample consisted of 38 DLB patients and 38 age-and sex-matched normal controls. We evaluated cognitive function using the Consortium to Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…8 Additionally, specific abnormalities of the pulvinar region were linked to Lewy body dementia associated with special cognitive impairments involving attention, and visuospatial and memory processes. 34,35 Briefly, our results suggest the pulvinar may play a role in AD-related cognitive impairment which, together with other critical regions, was affected in this study, and may contribute to cognitive deficits.…”
Section: Study Conclusion and Disease Implicationsmentioning
confidence: 56%
“…8 Additionally, specific abnormalities of the pulvinar region were linked to Lewy body dementia associated with special cognitive impairments involving attention, and visuospatial and memory processes. 34,35 Briefly, our results suggest the pulvinar may play a role in AD-related cognitive impairment which, together with other critical regions, was affected in this study, and may contribute to cognitive deficits.…”
Section: Study Conclusion and Disease Implicationsmentioning
confidence: 56%
“…Further, the MD nucleus has shown meaningful bilateral connections to the prefrontal cortex and the anterior cingulate cortex ( Eckert et al, 2012 ), regions strongly associated with executive function ( Carter et al, 1999 ; Friedman and Robbins, 2022 ). The Pulvinar nucleus is important for executive function ( Ouhaz et al, 2018 ), which have already been described as a factor that may contribute to dysexecutive function in other dementias ( Tak et al, 2020 ). This is in line with our results, as changes in the MD and the Pulvinar nucleus were associated with decreased cognitive flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…TA defines the measure of voxel intensities, voxel inter-relationships, and the gray-level patterns in the image. TA has been successfully used for characterizing multiple sclerosis (6)(7)(8), small vessel disease (9), and dementia with Lewy bodies (10). It has been demonstrated that TA is an effective tool for image analysis.…”
Section: Open Access Edited Bymentioning
confidence: 99%